Green Entrepreneurship Model in The Batik Industry: a Solution Towards Sustainable Development goals (SDGs) - Sudarmiatin, Sudarmiatin; Fitri, Raisa (Profesional Muda Cendekia Publishing, 2023)
Abstract Green Entrepreneurship (GE) seeks to integrate environmental and social benefits to provide competitive advantages for companies. The general aim of this research is to analyze problems and develop a green entrepreneurship model for the batik industry in Tulungagung district. Meanwhile, the specific objectives of this research are (1) to describe the implementation of green entrepreneurship in the batik industry in Tulungagung district. (2) describe the problems faced by batik craftsmen in Tulungagung district in implementing green entrepreneurship (3) develop a green entrepreneurship model through the four-D approach The research approach is a qualitative case study with the output of a green entrepreneurship model for the batik industry in Tulungagung district, East Java. The research subjects were batik industry managers, batik industry employees, and the local government as a policy-making agency, totaling 25 people. The instruments used in this research include interview guides, observation sheets and documentation. Meanwhile, data analysis uses the Miles, Huberman & Saldana (2014) formula. The research results show that the application of green entrepreneurship in the batik industry is still limited to the use of non-plastic packaging and Eco print batik innovation. The problems of batik craftsmen in implementing green entrepreneurship include not managing industrial waste properly, lack of green entrepreneurship literacy, lack of ongoing assistance and supervision. Green awareness of batik craftsmen is still low due to limited knowledge. Practical research suggestions still require socialization and assistance regarding the implementation of green entrepreneurship both from the local government and from other parties who care about environmental safety.